Knowledge on the Use of Biosimilars in Hematological Malignancies Amongst Health Care Workers at a Tertiary Hospital in Northeast Nigeria - Rufai A. Dachi; Mustapha S. Umar; Maryam Mahdi; Nura H. Alkali; Falmata G. Mustapha; Fatima M. Muhammad; Alhaji Abdu (International Journal of Medicine and Health Development)
Background: Hematological malignancies, like other cancers, are on the rise. Their treatments have been revolutionized using biological molecules (biologics and biosimilars). These novel agents are used in the care of cancer patients and have significantly improved survival. While biosimilars are widely available, their use is still limited in some low- and middle-income countries, including Nigeria. Objectives: To determine the knowledge of healthcare workers (HCWs) at a tertiary hospital in Bauchi, Nigeria, before and after a structured training program on the use of biosimilars in hematological malignancies. Materials and Methods: Healthcare workers underwent a week-long training on biosimilars. Knowledge of pre- and post-training was ascertained using interviewer-administered questionnaires. Participant data was summarized as percentages in charts and tables and compared using the Z-test in Microsoft Excel 2016. P values ≤ 0.05 were considered significant. Results: One hundred and sixty one (161) participants attended the training, with females constituting 56.5%. Participants’ knowledge of cancer and hematological malignancies was significantly higher after training (82.1% vs. 61.5%; Z = 4.12, P < 0.001). One hundred and forty (140) participants participated in the post-test. Similarly, the knowledge of biologics and biosimilars used in hematological malignancies was significantly higher after training (80.0% vs. 44.1%; Z = 6.62, P < 0.001). Conclusion: Knowledge of biosimilars and their use in hematological malignancies was low among HCWs but improved significantly after an educational training program.